Applying the technology acceptance model in analysing the impact towards the email usage among academicians in Pakistan and Malaysian public universities - Qadri, Hussain Mohi-Ud-Din; Mahomed, Anuar Shah Bali; Sheikh Mokhtar, Siti Salwa; Ahmad, Abd Rahman; Reza, Syahrul; Othman, Zulbasri (Science International, 2021)
Communication involves the intersection of two notions, specifically in an institution or organization. Thus, one of the main elements of transmitting information or increasing communication efficiency is email. Previously, email can be known as the new communication channel; however, align with the evolution, email is mostly known as part of welldeveloped and well-known communication through countries in the new era's transition. Therefore, this research attempted to identify the impact of the technology acceptance model on email usage among academicians in Pakistan and Malaysian public universities by applying the model of technology acceptance model derived by (Davis, 1989). This research adopts the TAM model elements: ease of use and perceived usefulness to measure the technology acceptance model's impact on email usage among academicians in Pakistan and Malaysian public universities. This study distributed 150 questionnaires between public universities in Pakistan and employed SmartPLS 2.0 for the SEM model estimation. It compared it with the previous data collected by the corresponding author of this article in his study on email usage among academicians in Malaysia. The findings show that, by using TAM's element, which is perceived ease of use and perceived usefulness, Pakistan academicians have lower PU, PEOU, and usage on overall email usage than Malaysia academicians. This study contributes to the literature and provides new insights by applying the model compared to two countries.